STUDI KOMPARATIF GAYA MENGAJAR GURU LAKI-LAKI DAN PEREMPUAN DI SDN 111 PEKANBARU DAN SDN 010 SERESAM - Anissa Miranda; Btari Maharani; Dinda Khoirunnisa Az-Zahra; Laila Alvi Syahrina; Muhammad Fendrik; Cici Oktaviani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine and analyze the differences in teaching styles between male and female teachers at SDN 111 Pekanbaru and SDN 010 Seresam. The research employed a quantitative comparative approach. The participants consisted of 10 teachers selected through purposive sampling, including 5 male teachers and 5 female teachers. Data were collected using a questionnaire developed based on indicators of basic teaching skills, such as questioning skills, explaining, reinforcement, classroom management, and the use of learning variations. The collected data were analyzed using descriptive statistics and Independent Sample t-test with the assistance of SPSS software. The descriptive analysis showed that the average teaching style score of male teachers was 66.6, while female teachers obtained an average score of 66.0. The results of the homogeneity test indicated a significance value of 0.112 (> 0.05), demonstrating that the data variance was homogeneous. Furthermore, the Independent Sample t-test produced a significance value (Sig. 2-tailed) of 0.870 (> 0.05), indicating that there was no significant difference in teaching styles between male and female teachers. The findings suggest that gender is not the primary factor influencing teaching styles in elementary schools. Instead, teaching competence, professional experience, and pedagogical skills play a more substantial role in determining the quality of classroom instruction. Therefore, efforts to improve educational quality should focus on enhancing teachers’ professional competencies regardless of gender.